OHS ANALYSIS TO UNSAFE ACTION IN KERTOSONO – JOMBANG – MOJOKERTO – GEMPOL ROAD AND BRIDGE PRESERVATION PROJECT - Anara Bhisma Soca Driya; Fadjar Purnomo; Mochammad Khamim (Jurnal Online Skripsi Manajemen Rekayasa Konstruksi (JOS-MRK), 2024)
Road preservation project is one of the large-scale construction activities. PT Abipraya is one of the well-known contractors that carries out the project, therefore a proper OHS (Occupational Health and Safety) regulations are very important to establish. In this study an analysis of several OHS factors will be carried out which are considered to reduce the occurrence of unsafe acts. The factor used is the variable X1 namely "OHS understanding" and X2 namely "Implementation of OHS" as the independent variable, and the Y1 variable namely "Worker Behaviour" as the dependent variable. Data anlysis will be done by using IBM SPSS statistics with validity tests, reliability tests, correlation tests, and multiple linear regression tests. The results show that the correlation value between the variables X1 and X2 is 0.771 included in the "strong" category, the X1 and Y1 variables are 0.274 included in the "weak" category, the X2 and Y1 variables are 0.464 included in the "moderate" category. The “t” test is used to show the partial effects between each independent variables to the dependent variables, and the result of the “t” value between variables X1 and Y1 of -0.887 which does not meet the requirements so that it does not have a significant impact on reducing unsafe acts. The result of the “t” value between the variables X2 and Y1 is 2,676 which already meets the requirements so that it has an impact on reducing unsafe acts. For the “F” test is used to show whether both independents variables have a simultaneous impact to the dependent variable, and the “F” value shows a result of 5,295 which meets the requirements so that variables X1 and X2 simultaneously have an impact on variable Y1. Based on the result, the value of OHS cost estimation already set as much as Rp. 2,491,303,048.96.